ABOUT INTEGRATION OF DISCIPLINES IN PHYSICS EDUCATION - O'razov, Abduxoliq; Dehqonova, Ohista; Mamatmuradova , Mohigul (Физико-технологического образование, 2021)
The problem of interdisciplinary integration in the educational system is investigated. It was shown that interdisciplinary integration is presented as a means of increasing students' independent creative abilities, increasing and shaping their worldview and scientific thinking, and ultimately improving the entire educational process